Storage methods and injection site preferences of patients with type 2 diabetes on insulin regimen in North-East Ethiopia: A qualitative inquiry - Ewunetie Mekashaw Bayked; Mesfin Haile Kahissay; Birhanu Demeke Workneh (Cogent Public Health)
: Insulin treatment is seriously influenced by the choice of injection site and storage practices. The study looked at the storage mechanisms and injection site preferences of type 2 diabetes patients at Dessie Comprehensive Specialized Hospital, in Dessie City Administration, North-East Ethiopia. We conducted a qualitative study from July 2019 to January 2020 on twenty-four (11 males and 13 females) participants who were recruited purposefully. Until theoretical saturation was reached, we collected the data through face-to-face, in-depth interviews that lasted about 23 to 71 minutes and organized it using QDA Miner Lite v2.0.9. We then thematically analyzed the transcripts and discussed the themes that arose in detail using narrative strategies. A jar filled with wet sand was the most common handling device for insulin, for both insulin in use and reserves, both at home and on the road. The most popular injection site was the abdomen, followed by the thighs and upper arms. With the container they indicated, it is unclear how the patients store insulin. The dangers of storing insulin at home are often disregarded, and better education is required. Practical advice on how to properly keep insulin at home is also essential.